Evaluation of the angiotensin-converting enzyme insertion/deletion polymorphism and the risk of ischaemic stroke - TUĞLULAR, ZÜBEYDE SERHAN (CHURCHILL LIVINGSTONE, 2006)
Angiotensin-converting enzyme (ACE) gene polymorphism has been associated with increased incidence of stroke in some populations, although contradictory results have been reported. The aim of this study was to determine the allelic frequency and the genotypic distribution for ACE gene polymorphism in Turkish patients with ischemic stroke compared to appropriate healthy controls and to correlate the genetic findings with stoke type. One hundred and eight patients with ischemic stroke versus 79 healthy controls were studied for the presence of ACE gene polymorphism detected by PCR. Genotypes were defined as DD, II and ID according to the presence of the D (deletion) and I (insertion) alleles. There was no statistically significant difference in either the genotypic distribution or allelic frequency between the patients versus healthy controls (chi(2) = 0.105; df = 1; p = 0.430). There was also no significant difference for ACE genotype distribution and allelic frequency within the stroke group classified according to Bamford criteria (chi(2) = 4.827; df = 3; p = 0.185). Our data supports lack of association between DD genotype and/or D allele and ischemic stroke or subtypes of ischaemic stroke in the Turkish population. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: angiotensin-converting enzyme; gene polymorphism; ischaemic stroke; allelic frequency; genotype; GENE POLYMORPHISM; ESSENTIAL-HYPERTENSION; DELETION POLYMORPHISM; CEREBROVASCULAR-DISEASE; MYOCARDIAL-INFARCTION; BRAIN INFARCTION; ARTERY-STENOSIS; ACE GENE; RENIN; ASSOCIATION